Zápas o šťastné dětství - Bittnerová, Dana; Levínská, Markéta; Doubek, David (Romano džaniben, 2017)
The contribution interprets the nature of the institution of childhood and the happy childhood cultural model from the perspective of the majority, which is represented by institutions of the modern state, and from the perspective of members of several particular Romani communities living in rural socially excluded localities. The data collection is based on ethnographic field research. We focused on the relations and interactions between helping professions and their Romani clients. In this article, we analyse the tensions arising from different emic perspectives on the institution of childhood. We present three different cultural models of childhood – that of the Romani parents, Czech teachers, and public officers (social affairs). We concentrate on the principles that create the discussed cultural models and we follow their immediate impact on the decisions of the research participants as actors in local reality. We study the processes involved in the negotiation of norms and what is and what is not considered to be the happy childhood.